Development of E-Module Based on Guided Discovery on Polyhedron Material for Eighth Grade - Harisman Nizar; Anita Umami; Yuli Fitrianti (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2026)
E-Modules are a form of independent learning media designed to cover a specific topic or material. This study aims to develop Canva-based mathematics learning media on the material of flat-sided solid shapes with a guided discovery approach that has a level of validity, practicality, and potential effects on improving students' conceptual understanding. The type of research applied is design research with a development study type, using the Tessmer procedure which includes two main stages, namely the preliminary stage and the prototyping stage through a formative evaluation process, which consists of self-evaluation, one-to-one, expert reviews, small group, and field test. The material in the e-module is arranged based on guided discovery indicators, while the evaluation tool is developed referring to the conceptual understanding indicators. Data collection techniques include interviews, tests, validation sheets, and questionnaires. The research subjects are grade VIII junior high school students. The results of the study indicate that the developed learning media has met the valid criteria based on the results of expert validation, practicality according to the results of student response questionnaires, and has a potential effect in improving students' mathematical conceptual understanding abilities.